Improvement of Asphalt-Aggregate Adhesion Using Plant Ash Byproduct - Liu, Zhuangzhuang; Huang, Xiaonan; Sha, Aimin; Wang, Hao; Chen, Jiaqi; Li, Cheng (Materials, 2019)
The adhesion bonding between asphalt and aggregate significantly influences field performance and durability of asphalt pavement. Adhesion promoters are typically used to improve asphalt-aggregate bonding and minimize moisture-related pavement damage, such as cracking and raveling. This study evaluated the effectiveness of plant ash byproduct as adhesion promoter to improve asphalt-aggregate adhesion performance. Three commonly used aggregate types (granite, basic rock, and limestone) and two asphalt binder types were used in laboratory testing. A modified stripping test method was developed to evaluate test results with image analysis and measurement of asphalt film thickness. The contact angle test and scanning electron microscopy (SEM) with energy disperse spectroscopy (EDS) were conducted. Test results showed that plant ash lixivium significantly improved asphalt-aggregate adhesion. Among three aggregate types, granite yielded the worst asphalt-aggregate adhesion for both control and treated specimens. The effectiveness of adhesion promotion varied depending on the type of asphalt or aggregate and temperature. The SEM/EDS observations showed that the mesh-like crystalline was formed at the interface between asphalt binder and aggregate in the treated specimen, which was believed to enhance the interfacial bonding and prevent asphalt film peeling off from aggregate.